The Effect of Low Doses of Memantine on Serum Levels of Inflammatory Mediators in Methadone-Dependent Rats - Bahareh Mortazavi; Zoya Tahergorabi; Omid Mehrpour; Mitra Moodi (مجله دانشکده پزشکی اصفهان, 2019)
Background: Opioid abuse is a major and challenging public health problem with a broad range of physical, mental, and psychiatric consequences worldwide. This study was designed to evaluate the effect of low doses of memantine on serum levels of inflammatory mediators in methadone-dependent rats.